2013
DOI: 10.1159/000356312
|View full text |Cite
|
Sign up to set email alerts
|

Lamivudine Treatment Failure Risks in Chronic Hepatitis B Patients with Low Viral Load

Abstract: Aim: To analyze the risk factors of lamivudine treatment failure (LTF) for the long-term use in patients with low viral load (LVL). Material and Methods: In this multicenter study, 548 antiviral naïve noncirrhotic adult patients with LVL (for HBeAg+ patients HBV DNA <109 copies/ml and for HBeAg- patients HBV DNA <107 copies/ml) were enrolled. As a control group, 46 lamivudine-initiated patients with high viral load (HVL) were included. Primary outcome was switching to or adding on another… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…reported that 13% of the patients who achieved complete viral suppression (HBV DNA < 200 copies/mL) with continuous lamivudine treatment developed viral resistance over a median follow‐up period of 12 months . In a recent multicenter study the lamivudine treatment failure rate was examined in 548 non‐cirrhotic patients (85% HBeAg‐negative) with a low viral load (for HBeAg‐positive patients, HBV DNA <10 9 copies/mL and for HBeAg‐negative patients, HBV DNA <10 7 copies/mL). A cut‐off value of <400 copies/mL was defined as early virological response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…reported that 13% of the patients who achieved complete viral suppression (HBV DNA < 200 copies/mL) with continuous lamivudine treatment developed viral resistance over a median follow‐up period of 12 months . In a recent multicenter study the lamivudine treatment failure rate was examined in 548 non‐cirrhotic patients (85% HBeAg‐negative) with a low viral load (for HBeAg‐positive patients, HBV DNA <10 9 copies/mL and for HBeAg‐negative patients, HBV DNA <10 7 copies/mL). A cut‐off value of <400 copies/mL was defined as early virological response.…”
Section: Discussionmentioning
confidence: 99%
“…Data have been scarce on the long‐term outcomes of treatment with lamivudine for patients with low baseline viremia plus an early virological response. A recent study showed there was a 5‐year treatment failure rate of 61.3% with lamivudine therapy among patients with a low pretreatment viral load (HBV DNA <10 7 and <10 9 copies/mL for patients with negative and positive hepatitis B e antigen [HBeAg], respectively) . The aim of this study was to assess the long‐term results and effectiveness of lamivudine treatment for patients with low pretreatment viremia and an early virological response to treatment.…”
Section: Introductionmentioning
confidence: 99%